1972
DOI: 10.1017/s0022377800006905
|View full text |Cite
|
Sign up to set email alerts
|

Current sheath studies in a co-axial plasma focus gun

Abstract: A co-axial plasma focus device is operated in deuterium gas at ambient pressures from 0·2 to 0·7 mm Hg and condenser bank voltages from 10 to 22 kV. Magnetic probing reveals an axisymmetric parabolic current sheath which propagates down the co-axial tube (steady propagation region) and collapses off the end of the co-axial gun forming a dense plasma focus. The state of the plasma just before the focusing action is very much dependent on the velocity in the steady propagation region. This velocity is experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 6 publications
(6 reference statements)
2
22
0
3
Order By: Relevance
“…In that work the simplest representation was used, in which the current sheet is shown to go from the anode to the cathode perpendicularly. Observation shows that there is actually a canting of the current sheet [53] and also that only a fraction (typically 0.7) of the total current participates in driving the current sheet. These points are accounted for in the modeling by model parameters f m and f c .…”
Section: The Cause Of Neutron 'Saturation' Is the Dynamic Resistancementioning
confidence: 99%
“…In that work the simplest representation was used, in which the current sheet is shown to go from the anode to the cathode perpendicularly. Observation shows that there is actually a canting of the current sheet [53] and also that only a fraction (typically 0.7) of the total current participates in driving the current sheet. These points are accounted for in the modeling by model parameters f m and f c .…”
Section: The Cause Of Neutron 'Saturation' Is the Dynamic Resistancementioning
confidence: 99%
“…Another important motivation in this paper is as follows: PF experiments have shown that there exist a certain mass loss in the inter-electrode region during the axial phase. In a typical experiment, at least 20 − 40% of the initial mass of the current sheath which is generated in the breakdown phase is lost [14][15][16]. In other words, a certain number of electrons and ions always escape from the spaces between the cathode rods while the plasma sheath moves.…”
mentioning
confidence: 99%
“…It can be seen from this figure that θ is damped with two regions, the first one from the breech until a distance Z ~ 4 cm and the second from Z ~ 4 cm to muzzle with different rates as follows: The above data show that, the rate of decreasing of angle θ with Z has approximately the same values for all gas pressures under consideration from the breech to Z = 4 cm, while at axial distance from 4 cm to muzzle, the rate of decreasing of θ with axial distance Z has a maximum value at P = 1.4 torr i.e. at this pressure the parabolic PCS profile is more canted than other gas pressure values under consideration, also this behavior could be owing to the fact that the magnetic pressure B 2 /2µ [3] has a peak value at this gas pressure value.…”
Section: Variation Of Ln(thickness Of Pcs λ In Arbitrary Unit) and Lmentioning
confidence: 84%
“…Several studies [2][3][4] which are related to PCS formation in coaxial plasma discharge device is accomplished by two basic processes, 1) the formation of an axisymmetric current sheath at the surface of the insulator end of the coaxial electrodes breech, 2) axial acceleration of PCS by the electromagnetic force ( r J B   ) along the annular of inter electrode discharge region.…”
Section: Introductionmentioning
confidence: 99%